A clinical case of asymptomatic pancreatic hyperenzymemia on the background of taking a Glucagon-like peptide-1 analogue (GLP-1) - N.A. Sanina; N.O. Hondulenko; S.S. Panina; V.S. Shulha (Medičnì Perspektivi)
According to current statistics, the incidence of type 2 diabetes has increased significantly over the past few years. The number of drugs prescribed to correct carbohydrate metabolism is also increasing, and new groups of hypoglycemic drugs are appearing. This prompts a more detailed study and analysis of the possible side effects of the prescribed therapy. One of the modern groups of medications f  or treating type 2 diabetes are analogues of glucagon-like peptide-1 receptor agonists, which, in addition to correcting carbohydrate metabolism, have a beneficial effect on the risk of developing cardiovascular events. Despite this, there is evidence that their use may be associated with the development of undesirable adverse effects from the pancreas, particularly acute pancreatitis, pancreatopathy, or asymptomatic hyperenzymemia. The aim of our work was the analysis of a clinical case of an asymptomatic increase in the level of pancreatic enzymes (Gullo's syndrome) in a patient with type 2 diabetes, who used a glucagon-like peptide-1 receptor analogue for treatment according to the usual scheme (dulaglutide 0.75 mg subcutaneously once a week during 2 years). As a result, the patient developed a side effect that could be related to taking this medicine. This did not lead to the withdrawal of the drug but required a more thorough examination of the patient and regular further screening for the timely detection of the development of possible organic pathology of the pancreas in the future. So, after analyzing this clinical case, it is possible to see the possibility of developing asymptomatic pancreatic hyperenzymopathy during the treatment of type 2 diabetes mellitus with glucagon-like peptide-1 receptor agonist analogues, which should be taken into account when determining the treatment tactics.